Vision-related quality of life and access to eye care among recently resettled Syrian refugees in Philadelphia - Sila Bal (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background Eye health is a major contributor to quality of life and remains a significant global health concern. Syrian refugees are at increased risk for worsening eye care due to the rapid loss of healthcare infrastructure. No studies to date have explored the visual needs and vision-related quality of life in refugee groups. # Methods Cross-sectional study of a convenience sample of recently resettled Syrian refugees recruited through Nationalities Service Center in Philadelphia, PA. We developed a 53-item survey comprised of questions from previously validated questionnaires, including the Arabic Behavioral Risk Factor Surveillance System and the Arabic Visual Function Questionnaire-25 (VFQ). The primary outcomes were self-reported visual impairment, VFQ composite and sub-scale scores, and eye care access. # Results Seventeen adults and six children completed the surveys. The average time since resettlement was 20.5 weeks (standard deviation=12.9). Six (35.2%) of the participants reported ocular pathology. Five (29.4%) had never had their eyes checked by their primary care provider. The mean VFQ composite score was 69.4 (standard deviation=22.1). Six participants (35.2%) cited cost and lack of knowledge of health resources as the most common barriers to eye care. There were significant differences in VFQ sub-scale scores related to age and time since resettlement (*P\>*0.05). # Conclusions Syrian participants reported poor eye care access and disproportionately low vision-related quality of life when compared to other working age populations from the literature. Our study highlights the need for improved resources surrounding visual health and eye care access among resettled Syrian refugees.